Construction of an eco-friendly water treatments method by utilizing recycled materials- A review. - Dixit, Krishna; Sheet, Simanta; Mishra, Mohit (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The most problematic issue of rural areas is the provision of clean water at a relatively low cost and energy rates. Industries discharge chemical effluents that contaminate existing water bodies. Chlorination may be one solution but are not employed in mass as they are less convenient to use. People die out of water borne diseases which in itself act as a source of motivation for resolving and analyzing the problem as soon as possible. In the present article, the demand of water treatment process that is chemical free, inexpensive, and simple to build has been increasing with the rise in population and pollution levels has been reviewed.